Journey Into the User Experience: Creating a Library Website That’s Not for Librarians - Murdoch, Craig; Hearne, S (VALA - Libraries, Technology and the Future Inc., 2014)
Auckland University of Technology Library started work on a major redevelopment of its website in 2012. The problem was that the website content, as is the case for many library websites, had been written by librarians with almost no user input. The challenge was to redesign the website, rethinking our entire focus and placing the user at the centre of the process. This is the story of a journey of transformational change based on our user-centric approach. We believe we have achieved what we set out to do and created a website that’s built not for librarians but for users.
Keywords: User experience; Library websites